Merajut Harmoni Sosial Dalam Masyarakat Melalui Pendekatan Participatory Rural Appraisal (PRA) - Putri, Elivia Pasma; Kurnia, Heri; Saryono; Jayawardana, Hepta Bungsu Agung (CV. Kurnia Grup, 2025)
The community service carried out by the author aims to find out how to weave social harmony in the community in Hamlet 3, Pulau Semambu Village, through the Participatory Rural Appraisal (PRA) approach. The Participatory Rural Appraisal (PRA) approach is a method that is closer to the active participation of the target group during the activity process. The method used in the village development activities is based on active participation aimed for 3 months from October to December 2024, with a focus on 3 main divisions, namely environment, health, and education. Village development is carried out by dividing activities into preparation, program implementation, and evaluation with local parties. The results of the village development activities have had a positive impact, with more than 60% of students understanding the material that has been presented and giving a good impression of what has been provided by the Village Development Volunteer Team. The Village Development program's follow-up results include Sriwijaya University's collaboration in the PPK Ormawa program, under the auspices of KEMDISTISAINTEK. Village development activities in Hamlet 3, Pulau Semambu Village are expected to create an independent, intelligent, healthy and noble village based on Islamic values.